The The Total Leukocytes Count and Leukocytes Diferential to effect of injection Multiantigens on male quail (Coturnix Coturnix japonica) - edhita daryanti (Jurnal Biogenerasi, 2021)
Poultry became a promising commodity in the farm. One of these types of birds is quail. Preventive efforts in the disease of poultry can be performed by vaccination. Vaccination is done by introducing disease agents by induing antigen into the poultry body so that the mortality rate against a particular disease decreases. The study aims to determine the effect of Multiantigen injection on the total number of leukocytes and differential leukocytes in male quail. The study used the experimental method of complete random draft (RAL) with animals as many as 28 male quail tails divided into 7 groups with 4 repeats, ie K0: uninjected antigen,, P1: Injection SDMD 4th week, P2: Vaccine injection ND 4th week, P3: injection of SDMD 2nd week and ND vaccine injection of the 4th week, Q4: Vaccine injection ND Week 2 and SDMD Injection Week 4, P5 : The 2nd week SDMD injection and SDMD injection of the 4th week, P6:2nd week ND Vaccine injection and the 4th week ND vaccine injection. Data are the total number of leukocytes and differential leukocytes. Data is analyzed with analysis of variants (ANOVA) using MiniTab17. Results showed that the total number of leukocytes and differential leukocytes is not significantly different (P > 0.05) with the treatment of control so that it can be concluded the effect of injection of multiantigen does not affect the total number of leukocytes and differential leukocytes in male quail.